Project Sponsorship in Recovering Delayed Projects: A Case Study from Korek Telecom: Sponsor Proyek dalam Pemulihan Proyek yang Tertunda: Studi Kasus dari Korek Telecom - Soha Mohsin; Fadia Adnan Qahtan (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Project management literature recognizes project sponsors as key stakeholders responsible for strategic guidance and executive support throughout the project lifecycle. Specific Background During periods of crisis such as the COVID-19 pandemic and regional political instability, many telecommunications projects experienced severe delays and declining stakeholder confidence. Knowledge Gap Although prior studies emphasize the strategic importance of project sponsors, limited research explains how sponsor involvement contributes to recovering delayed internal projects during crisis conditions. Aims This study examines the role of project sponsorship in managing the recovery of a delayed internal project at Korek Telecom. Results The findings show that active sponsor engagement strengthened stakeholder coordination, improved communication channels, and restored organizational trust during the recovery process. The sponsor also assumed operational leadership responsibilities by guiding process redesign, managing risks, and aligning team roles through structured governance tools such as the revised business case, work breakdown structure, RACI matrix, compressed project schedule, and risk register. Novelty The study highlights a dual sponsorship model in which the project sponsor functions not only as a strategic authority but also as an operational leader during project recovery. Implications These findings provide practical insights for telecommunications organizations and other industries by demonstrating how sponsor-led governance mechanisms support structured decision-making and coordinated recovery strategies in delayed projects. (219 words) Keywords: Project Sponsorship, Delayed Projects, Telecom Project Management, Project Recovery, Risk Governance Key Findings Highlights Sponsor leadership supported coordinated recovery actions during a delayed telecom project. Governance tools structured team alignment, accountability, and risk management. Strategic authority combined with operational guidance during crisis project recovery.